2023
DOI: 10.3390/su151712927
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality, Institutions, and Freedom of the Press: Potential Mechanisms and Evidence

Umut Uzar

Abstract: In the last few decades, income distribution has deteriorated in a large part of the world. The inability to stop inequality has evolved into a major social crisis and has become one of the most urgent issues globally. Given the importance of the issue, identifying the root causes of inequality can be a guide for policy makers in solving the problem. Although there are a few studies linking institutional quality with income inequality in recent years, the question of whether freedom of the press affects income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Institutional capacity measured by corruption and government effectiveness was found not to affect income inequality in the global sample; however, significantly, the coefficients of the interactions between institutional capacity and fiscal policy bear the expected signs, although insignificant. In the work of [ 75 ], a first attempt was made to address the question of whether institutions and freedom of the press affect income distribution in BRICS-T (Brazil, Russia, India, China, South Africa, and Turkey) countries from 1993 to 2016, and found that institutional quality and freedom of the press reduce income inequality. An augmented mean group (AMG) was employed to estimate the long-run relationship between institutions, freedom of the press and income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Institutional capacity measured by corruption and government effectiveness was found not to affect income inequality in the global sample; however, significantly, the coefficients of the interactions between institutional capacity and fiscal policy bear the expected signs, although insignificant. In the work of [ 75 ], a first attempt was made to address the question of whether institutions and freedom of the press affect income distribution in BRICS-T (Brazil, Russia, India, China, South Africa, and Turkey) countries from 1993 to 2016, and found that institutional quality and freedom of the press reduce income inequality. An augmented mean group (AMG) was employed to estimate the long-run relationship between institutions, freedom of the press and income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%